(untitled) (Experimental biology, 2009)
Influence of сarbon tetrachloride to erythrocyte membrane of rat was investigated in vivo. It was shown, that acute and chronic influence of сarbon tetrachloride causes increasing of hemolysis and decreasing antioxidant ferment catalase activity of erythrocyte membrane.